Peningkatan Hasil Belajar Pembelajaran Tematik Terpadu dengan Model Kooperatif Tipe Group Investigation Di SD - Asra Pratiwi; Yunisrul Yunisrul (Universitas Negeri Padang, 2021)
The purpose of this study is to describe the improvement of integrated thematic learning outcomes with the Group Investigation type Cooperative learning model in class IV SDN 17 Bonjo Alam Agam Regency. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teachers and 25 students. The results showed the value of planning learning cycle I 82.95% and increasing cycle II 95.45%. The observations of aspects of the first cycle of teachers were 83.32% and the second cycle increased by 94.44%. The results of observations of the aspects of students in the first cycle were 83.32% and increased in the second cycle 94.44%. The results of the study showed an increase in the learning outcomes of students from the first cycle namely 75 (Fair category) to 90 (Very Good category) in the second cycle. concluded in the study that learning with the Group Investigation type Cooperative model can improve the learning outcomes of thematic learning in elementary schools.